High RhoA activity maintains the undifferentiated mesenchymal cell phenotype, whereas RhoA down-regulation by laminin-2 induces smooth muscle myogenesis - Beqaj, Safedin (The Rockefeller University Press, 2002)
Round embryonic mesenchymal cells have the potential to differentiate into smooth muscle (SM) cells upon spreading/elongation (Yang, Y., K.C. Palmer, N. Relan, C. Diglio, and L. Schuger. 1998. Development. 125:2621–2629; Yang, Y., N.K. Relan, D.A. Przywara, and L. Schuger. 1999. Development. 126:3027–3033; Yang, Y., S. Beqaj, P. Kemp, I. Ariel, and L. Schuger. 2000. J. Clin. Invest. 106:1321–1330). In the developing lung, this process is stimulated by peribronchial accumulation of laminin (LN)-2 (Relan, N.K., Y. Yang, S. Beqaj, J.H. Miner, and L. Schuger. 1999. J. Cell Biol. 147:1341–1350). Here we show that LN-2 stimulates bronchial myogenesis by down-regulating RhoA activity. Immunohistochemistry, immunoblotting, and reverse transcriptase–PCR indicated that RhoA, a small GTPase signaling protein, is abundant in undifferentiated embryonic mesenchymal cells and that its levels decrease along with SM myogenesis. Functional studies using agonists and antagonists of RhoA activation and dominant positive and negative plasmid constructs demonstrated that high RhoA activity was required to maintain the round undifferentiated mesenchymal cell phenotype. This was in part achieved by restricting the localization of the myogenic transcription factor serum response factor (SRF) mostly to the mesenchymal cell cytoplasm. Upon spreading on LN-2 but not on other main components of the extracellular matrix, the activity and level of RhoA decreased rapidly, resulting in translocation of SRF to the nucleus. Both cell elongation and SRF translocation were prevented by overexpression of dominant positive RhoA. Once the cells underwent SM differentiation, up-regulation of RhoA activity induced rather than inhibited SM gene expression. Therefore, our studies suggest a novel mechanism whereby LN-2 and RhoA modulate SM myogenesis.